Incidence of Intralabyrinthine Schwannoma: A Population-based Study Within the United States. Issue 9 (October 2018) - Marinelli, John P.; Lohse, Christine M.; Carlson, Matthew L.
Abstract : Objective: To describe the incidence of intralabyrinthine schwannoma (ILS) utilizing the Rochester Epidemiology Project (REP), a unique medical consortium in the United States that covers a complete population of all ages in a well-defined geographic area over the past half-century. Patients: All patients with ILS diagnosed between January 1, 1966 and December 31, 2016 in Olmsted County, Minnesota, identified using the REP medical records-linkage system. Main Outcome Measures: Incidence of ILS. Results: Fourteen incident cases of ILS were identified in Olmsted County since 1966—a period spanning 5.9 million person-years. Over the past decade, the incidence rate of ILS was 0.81 per 100, 000 person-years and 1.1 over the last 5 years. Since 1966, the cumulative incidence rate of ILS over the past 50 years was 0.26 per 100, 000 person-years. The median age at diagnosis was 60 years (interquartile ranges, 39–70). Incidence increased with age: over the last 5 years, those aged 60 to 69 exhibited an incidence rate of 2.7 per 100, 000 person-years and those 70+ displayed a rate of 4.1. All patients had varying levels of asymmetrical sensorineural hearing loss with 64% of patients presenting with class D hearing. Four (29%) patients had a history of sudden sensorineural hearing loss, five (36%) reported imbalance and/or vertigo, and four (29%) reported aural fullness. Three of the 14 (21%) patients had neurofibromatosis type 2. Conclusion: The incidence of ILS exceeds 1 per 100, 000 person-years with modern diagnostic imaging. The rising incidence of ILS in recent years most likely reflects improved capacity for disease detection rather than a true increase in tumor development. Given the reputability of the REP consortium, these data suggest that ILS comprises a more common entity than previously considered.